2015
DOI: 10.5352/jls.2015.25.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation Properties and Inflammatory Cytokines Modulating of Fermented Milk with Curcuma longa L Powder

Abstract: Curcuma longa L. (CL), a traditional medicinal plant, is well known as a functional food ingredient. The major component of CL is a curcumin of anthocyanin family that has multi-functions such as antimicrobial, anticancer, and antioxidant activity. In this study, fermented milk containing CL was prepared using a mixed strain culture (Bifidobacterium bifidus, Streptococcus thermophilus, Lactobacillus acidophilus), and its physicochemical properties were characterized. In addition, inflammatory cytokine-modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The production of a fermented milk containing up to 3% turmeric was also reported (Gereltuya et al, 2015). In the current study, an was in the range of 1.80×10 9 _ 6.50 × 10 8 CFU/g, depending on the MSG concentration used (Table 1).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The production of a fermented milk containing up to 3% turmeric was also reported (Gereltuya et al, 2015). In the current study, an was in the range of 1.80×10 9 _ 6.50 × 10 8 CFU/g, depending on the MSG concentration used (Table 1).…”
Section: Resultsmentioning
confidence: 71%
“…The production of a fermented milk containing up to 3% turmeric was also reported (Gereltuya et al, 2015). In the current study, an alkaline fermentation of a high concentration of turmeric (50% of the turmeric/soybean substrate) was successfully carried out by B.…”
Section: B Subtilis Decreased As the Msg Concentration Increased (Unmentioning
confidence: 84%
See 1 more Smart Citation
“…Uniquely, these samples were slightly bitter compared to all other samples. The turmeric flavor might have caused the higher bitterness in these samples (Gereltuya et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The complex of the bioactive form of curcumin and milk proteins is able not only to provide preventive direction to the fermented milk drink but also to show a synergistic effect together with lactic acid bacteria, thereby increasing their vital activity ( 33 ). Thus, Abdelrazik and Fouad M. F. Elshaghabee ( 29 ) reported that the addition of curcumin at different concentrations led to a significant increase in antibacterial activity against gram-positive bacteria B. subtilis and S. aureus , as well as gram-negative E. coli and P. fluorescens ( 30 ).…”
Section: Introductionmentioning
confidence: 99%